Pengaruh Harga terhadap Kepuasan Pelanggan melalui Electronic Word of Mouth sebagai Variabel Mediasi pada Usaha Dekorasi Cutey Lasting Fleur - Putra, Bintang Damara Regaswara S.; Putri, Putu Riana Artyanti (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of price on customer satisfaction with electronic word of mouth (e-WOM) as a mediating variable at Cutey Lasting Fleur, a decoration business located in Denpasar. The research is motivated by customer complaints regarding price–value mismatch and negative online reviews, which have the potential to affect the company’s image. This research employs a quantitative approach using Partial Least Squares – Structural Equation Modeling (PLS-SEM) for data analysis. Primary data were collected through a Likert-scale questionnaire distributed to 140 respondents who had previously used Cutey Lasting Fleur’s services. The results are expected to reveal the direct influence of price on customer satisfaction and the mediating role of e-WOM in strengthening this relationship. Theoretically, this study contributes to marketing management literature, particularly in understanding consumer behavior and digital communication. Practically, the findings are expected to serve as a strategic reference for decoration service providers in designing fair pricing strategies that enhance customer satisfaction and foster positive online word of mouth.